An analysis of computer literacy levels among pre-service teachers in the university of Ibadan Open Distance Learning (ODL) programme (2016)
Teacher certification is a core concern for educational planners and employers of labour in Nigeria with the adoption of the National policy on education in 1981 that made the Nigeria Certificate in Education (NCE), least teaching qualification. Employers have sought ways of improving teacher qualifications while planners have sought ways of increasing teacher production to meet rising demands. Distance education adopted by the University of Ibadan utilizes Information Communication Technology (Computers, laptops, smartphones and the internet). Distance education adopts high computer literacy skills to ensure students competence in their studies. This paper investigated computer literacy levels among pre-service teachers in the University of Ibadan ODL using the survey research design. The study population consisted of students in the 8 Departments of the Faculty of Education involved in the ODL using the disproportionate stratified random sampling technique to select 500 respondents. A researcher developed instrument 'Pre-service Teachers Computer Literacy Level Assessment Questionnaire (PTCLLAQ r=0.85) was adopted for the study. Findings indicated that a significant positive relationship r=0.025; p<0.05 existed between computer literacy level and ODL programme at the University hence the study recommended that the centre should find ways to sustain the current trend.